2020
DOI: 10.1002/pc.25580
|View full text |Cite
|
Sign up to set email alerts
|

Acetylated cellulose nanostructures as reinforcement materials for PBAT nanocomposites

Abstract: Acetylated‐cellulose nanostructures (CNS) were used as reinforcing agent to develop poly(butylene adipate‐co‐terephthalate)—PBAT—nanocomposites with 1, 3, 5, and 10 wt% of modified and nonmodified nanoparticles through solvent casting. This study explains the interactions between the reactive groups CNS and PBAT interact and the influence of this interaction in the mechanical and thermal properties of the composites. The nonmodified CNS showed a noncontinuous increase in the PBAT stiffness, due to the low inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…This is because, if antimicrobial packaging is made from a combination of antimicrobial agents and materials that are based on renewable raw materials, it may accelerate the biodegradation process and further stabilize the ecosystem balance. These results suggest that antimicrobial packaging is not only able to show the ability of controlling the growth of microorganisms and prolonging the shelf life of food, which is very important in food safety, but also has a positive effect on the environment [129]. Many studies have been conducted on the mechanism of silver nanoparticles as an active packaging ingredient in packaging [53,55,58,[133][134][135][136][137][138][139].…”
Section: Performance Of Antimicrobial Packagingmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because, if antimicrobial packaging is made from a combination of antimicrobial agents and materials that are based on renewable raw materials, it may accelerate the biodegradation process and further stabilize the ecosystem balance. These results suggest that antimicrobial packaging is not only able to show the ability of controlling the growth of microorganisms and prolonging the shelf life of food, which is very important in food safety, but also has a positive effect on the environment [129]. Many studies have been conducted on the mechanism of silver nanoparticles as an active packaging ingredient in packaging [53,55,58,[133][134][135][136][137][138][139].…”
Section: Performance Of Antimicrobial Packagingmentioning
confidence: 99%
“…Bacterial or microbial cellulose has gained attention for humidity sensor use over the last decade [118,119,[128][129][130][131][132][133][134][135][136]. This type of cellulose is derived from the bacteria cultivated under appropriate conditions.…”
Section: Pani/bacterial Cellulose Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of cellulose micro- and nanomaterials, the esterification is the second most popular method after adsorption [ 129 , 130 , 131 , 132 , 133 ]. Some of the selected studies are summarized in Table 4 .…”
Section: Modification Of Cellulose Micro- and Nanomaterialsmentioning
confidence: 99%
“…20,21 Likewise, studies have shown that CNFs with large aspect ratio exhibit a potential in polymer enhancement. [22][23][24] Neto et al used CNCs as a reinforcing material in CMC matrix, and pointed out that the mechanical properties and thermal stability of composite films were apparently improved. 14 Later, Oun et al isolated CNFs from cotton linter pulp and evaluated the effect on CMC films, demonstrating that the tensile strength (TS) and elastic modulus (EM) of CMC film were improved by 23% and 27%, respectively.…”
Section: Introductionmentioning
confidence: 99%